Formation and characterizations of ultra-shallow p(+)-n junctions using B10H14 ion implantation - Jeon, GY; Kim, JS; Whang, CN; Im, S; Song, JH; Song, JH; Choi, WK; Kim, HK (ELSEVIER SCIENCE BV, 2003)
We report on the ultra-shallow p(+)-n junction formation by decaborane (B10H14) ion implantation into n-Si(100) substrates. The implantation energies of 5, 10 and 15 keV were used with the doses of 1 x 10(12) and 1 x 10(13) cm(-2). The implanted samples were then subject to activation-annealing at 800, 900 and 1000 degreesC for 10 s. According to the results of secondary ion mass spectrometry, the p(+) layer thinner than 50 nm formed in most of the samples. Current-voltage (I-V) measurements performed on the p(+)-n junction exhibited that the minimum leakage current density at -5 V was similar to10(-6) A/cm(-2) when the decaborane of 1 x 10(13) cm(-2) was implanted, while the maximum activated carrier dose of p(+) layers was measured up to 8.1 x 10(13) cm(-2) by Hall measurements. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: BORON